Fluoride removal in drinking water by precipitation-flocculation with aluminum polychloride and lime milk (Revista Ciencia Agraria, 2022)
The study consisted of evaluating the percentage of fluoride removal from drinking water by precipitation and flocculation with aluminum polychloride and lime milk. The research includes the treatment of well water from the highlands which was carried out at the laboratory level in order to remove fluoride from drinking water. According to the monitoring carried out, the water from the Taraco well contains 2.23 mg/L of F and the water from the Juli well contains 2.20 mg/L of F. The results of the fluoride removal process with poly aluminum chloride were 56 %, with a reduction from 2.23 mg/L F to 0.98 mg/L F. During the flocculation process, the pH, time and stirring speed were controlled. The removal of fluoride with milk of lime has been reduced from 2.23 mg/L of F to 1.5 mg/L of F. The experimental tests of precipitation and flocculation were carried out in the quality control laboratory of the Faculty of Chemical Engineering. The equipment used is Test Jar and pH meter. Regarding the statistical method, the 2' factorial design has been used, which has allowed optimization of the parameters of the flocculation process.
Keywords: fluoride; polyaluminum; chloride; lime; coagulation; flocculation